Avaliações SAEB e SEAMA: Uma análise estatística em Santana do Maranhão – MA - JÚNIOR, Eudes Nascimento Silva (2024)
This dissertation presents a detailed statistical analysis of the average mathematics proficiency levels of middle school students in Santana do Maranhão, using data from the Basic Education Evaluation System – SAEB) and the Maranhão State Evaluation System – SEAMA to assess student performance from 2005 to 2023. The focus is particularly on the impact of the COVID-19 pandemic on the Basic Education Development Index – IDEB, comparing average proficiencies before and after the pandemic period. The research identifies a trajectory of growth in average mathematics proficiency until 2019, when students achieved an average score of 249.3 points. Following the pandemic’s impact, the data reveal fluctuations: although the average dropped to 241.85 points in 2021, a recovery was observed by 2023, with an average of 256.83 points. This increase suggests a resumption of educational development in the municipality, though the pace of progression was affected. The quantitative analysis highlights both the challenges and recoveries in learning, focusing on factors contributing to the interruption in growth in 2021 and the strategies that enabled subsequent recovery. This research contributes to the debate on teacher training and its relationship with student performance in large-scale assessments, offering practical recommendations for improving public education policies in Santana do Maranhão – MA.